The Use of Cake Application in Learning English Speaking Skills - Rahmawati, Lela; Hastuti, Hilda; Syahid, Agus; Sutarman, Sutarman; Alfilail, Nur (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to investigate the effectiveness of using the CAKE application in improving the English language skills of Bumigora University students. This research was conducted through a Classroom Action Research (CAR) model, which consists of two cycles. Each cycle involves four stages: planning, action, observation, and reflection, involving 40 students of the Information Technology Study Program. Data collection techniques used in this study were a Speaking Ability Test, Observation, Questionnaires, and Interviews. The results of the study showed a significant increase in students' speaking skills after using the CAKE application as a learning medium. The average pre-test score of 54.90 indicated that students' initial abilities were still in the low category. After the implementation of the action in cycle I, the average score increased to 66.82, indicating initial improvements in the aspects of pronunciation, fluency, and students' confidence in speaking. In cycle II, the average score increased again significantly to 79.28, indicating that the consistent use of the CAKE application had a positive impact on the development of students' speaking skills. Thus, this study concludes that CAKE is an effective and relevant digital learning medium in supporting the mastery of EFL students' speaking skills, especially in the context of technology-based learning in higher education.